Applying radiobiological plan ranking methodology to VMAT prostate SBRT. Issue 4 (April 2016) - Stavrev, P.; Ruggieri, R.; Stavreva, N.; Naccarato, S.; Alongi, F.
Highlights: An application of an easy procedure for RT plan comparison is demonstrated. Matlab code is presented. The use of rectal spacer leads in general to improved tumor control. The use of rectal spacer lowers considerably the NTCP. The increased near maximum target dose plans proved superior in TCP and NTCP terms. Abstract: The impact of a rectal spacer and an increased near maximum target dose in VMAT prostate SBRT is studied. For a group of 11 patients (35 Gy-in-five-fractions VMAT prostate SBRT) a set of 4 plans were generated, namely two VMAT plans, with D2% ⩽ 37.5 Gy ( Hom ) and with D2% ⩽ 40.2 Gy ( Het ), were created for each of two CT scans taken before ( NoSpc ) and after ( Spc ) transperineal spacer insertion. Consequently the methodology for parameter invariant TCP (tumor control probability) plan ranking was applied for comparison of the plans in terms of tumor control. NTCPs (normal tissue complication probabilities) were calculated for rectum and bladder using Lyman's model. For all 11 patients the TCP plan ranking has shown that the Het plans would perform considerably better in TCP terms than the Hom ones. The plans without rectal spacer were ranked worse compared to those with rectal spacer except for one set of Hom plans. The calculated NTCPs for rectum produced by the Het plans were quite similar to the NTCPs of the Hom ones. The rectal NTCPs of the Hom Spc plans were always lower than the NTCPs of the Hom NoSpc plans. The NTCP values for bladder were extremely low in all cases. The use of rectal spacer leads in general to lower risk of rectal complications, as expected, and even to better tumor control. Plans with increased near maximum target dose (D2% ⩽ 40.2 Gy) are expected to perform much better in terms of tumor control than those with D2% ⩽ 37.5 Gy.